Effect of acupuncture on in vitro fertilization: An updated systematic review and data mining protocol. Issue 24 (June 2018) - Wang, Xiaotong; Lin, Haixiong; Chen, Mingzhu; Wang, Jian; Jin, Yuanlin
Abstract: Background: Although many patients try to seek acupuncture to improve in vitro fertilization (IVF) outcomes, evidence regarding its efficacy and acupoints characters are lacking. The aim of this protocol is to evaluate the effectiveness and safety, as well as the acupoints characteristics of acupuncture in the treatment of female undergoing IVF, by conducting a systematic review and data mining. Methods: The following 6 databases will be searched from their inception to April 30, 2018: PubMed, Chinese National Knowledge Infrastructure, Wanfang, VIP database, Embase, and Cochrane Library. The randomized controlled trials (RCTs) or case–control studies of acupuncture that assess clinical effects and side effects in female undergoing IVF are included. The primary outcome measures will be number of oocytes retrieved, fertilization rate, oocyte cleavage rate, high-quality embryos rate, ovarian hyperstimulation syndrome (OHHS) incidence rate, clinical pregnancy rate (CPR), biochemical pregnancy rate (BPR), implantation rate, and cycle cancellation rate. Two reviewers will independently undertake data extraction and quality assessments. Data will be synthesized by RevMan V.5.3 software. Acupoints characteristics will be excavated using Traditional Chinese Medicine inheritance support system (TCMISS). Reporting bias will be assessed by Funnel plots, Begg test, and Egger test. Results: This review will assess the clinical efficacy and safety, as well as the acupoints characteristics of acupuncture on IVF. Conclusion: These findings will summarize the current evidence of acupuncture on IVF outcomes and may provide guidance for clinicians and infertile women to select acupuncture for IVF. Abstract : Supplemental Digital Content is available in the text